Pyroclasts of the first phases of the explosive-effusive PCCVC volcanic eruption: physicochemical analysis - Botto, Irma Lía (2015)
The morphology, texture, grain size and other physicochemical characteristics of pyroclastic material from the first phases of the Puyehue-Cordon Caulle volcanic complex (PCCVC) eruption, (Southern Andes, Chile), can be associated to the model recently reported for the magma storage and its ascent conditions. The eruption started June 4th 2011, and the studied volcanic material corresponds to that collected in Argentine territory at different distances from the source, between 4 and 12 June 2011. The explosive-effusive volcanic process of the first days occurred with the simultaneous emplacement of lava flows and the venting of pyroclastic material, ejecting two well differentiated types of particles. The more abundant was constituted by rhyolitic and light color pumice fragments, characterized by a typical vesicular texture, easy fragmentation and absence of occluded crystalline phases. Particles found in minor proportion were dark color, different in shape and texture and rich in Fe and Ti. They seemed to be more effective for the interaction with emitted gases in the upper part of the column, for this reason, they appeared partially covered by condensation products. The ascent conditions of the magma affected its rheological behavior through variations in the degassing, viscosity and fragmentation. On the other hand, distance to the source, depositional time, volcanic evolution and environmental conditions are factors that affect the chemical composition of collected ash. So, the SiO2/FeO ratio not only increases with the distance but also with the deposition time and volcanic activity. The work was done with the aid of several techniques such as a laser-sediment analyzer, X-ray diffraction (XRD), chemical analysis (bulk and surface), SEM microscopy and Raman “microprobe” spectroscopy. On the other hand, the physicochemical behavior of the pyroclastic material allows us to suggest eventual applications.